The Non-injured Leg Can Be Used as a Reference for the Injured Leg in Single-legged Hop Tests - Astrid Vereijken; Emiel van Trijffel; Inne Aerts; Bruno Tassignon; Jo Verschueren; Romain Meeusen (International Journal of Sports Physical Therapy)
# Background Single-legged hop tests are frequently used in substantiating return to sport decisions following lower extremity injury. Evidence for using the non-injured leg as a reference for the injured leg in the return to sport decision-making at the criterion-based point of return to sport following lower extremity injury is lacking.